TGFβ-1 and ALK5 inhibitor treatment affects expressions of TGF β signalling pathway associated molecules in SHED cultured in keratinocyte growth medium - Mokhtar@Makhtar, Khairani Idah; Azmi, Nur Izyan; Berahim, Zurairah; Kannan, Thirumulu Ponnuraj; Ahmad, Azlina (2015)
Stem cells from human exfoliated deciduous teeth (SHED) can be induced to differentiate into epithelial-like cells when cultured in a differentiation medium. Transforming growth factor beta (TGF-β) signalling pathway plays an important regulatory function in epithelial proliferation and differentiation.TGF-β1 functions through a complex mechanism consisting of TGFβ type II and type I (ALK5) receptor to initiate cellular processes which could be inhibited by SB431542 molecule (ALK5 inhibitor). This study aims to analyse the expression of TGF-β signalling pathway associated molecules, ALK5 and Smad4, in SHED cultured in keratinocyte growth medium (KGM), treated with exogenous TGF-β1 and ALK5 inhibitor. SHED was cultured in KGM treated with TGF-β1 or ALK-5 inhibitor. RNA was extracted on cells harvested on day 1, 3, 7, 14 and 21 and subjected to reverse transcriptase-PCR using specific primers for ALK5, Smad4 and stem cell marker (Nanog). PCR products were electrophoresed on a 2% agarose gel stained with SYBR green. Nanog expression was maintained from day1 to 14 in all samples but was down regulated at day 21. ALK5 was expressed in most of the samples analysed from day 1 to 14 and down regulated at day 21. Smad4 expression was up regulated at day 1 to 3, down regulated from day 7 to 14 and lost its expression at day 21. TGFβ-1 and ALK5 inhibitor treatment affects the expressions of Nanog, ALK5 and Smad4 in SHED cultured in KGM. The involvement of these molecules during the differentiation process of SHED into epithelial-like cells will contribute further in the fundamental aspects of tissue regeneration research and highlights the importance of dental pulp stem cell technology.